RENDIMENTO DE GRÃOS EM LINHAGENS DE AVEIA BRANCA (Avena Sativa L.) CONDUZIDA SOB ESPAÇAMENTO ENTRE LINHAS REDUZIDO - Soares, Rômulo D.; Valentini, Ana P. F.; Gaviraghi, Fernando; Martins, João A. K.; Zambonato, Felipe; Wagner, Juliano F.; Battisti, Gabriel K.; Silva, Adair J. d.; Fernandes, Sandra B. V.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo